Increased sugar concentration in response to a wide range of pollinator sounds can be adaptive for the plant: answer to Raguso et al. (23rd June 2020) - Veits, Marine; Khait, Itzhak; Boonman, Arjan; Sharabi, Gayl; Sapir, Yuval; Yovel, Yossi; Hadany, Lilach
Abstract: In Veits et al., we showed that flowers respond to a range of pollinator sounds by increased nectar sugar concentration. Here we clarify that (1) our argument is relevant to most pollinators, and not limited to bees (2) specifically, bees do access Oenothera Drumondii nectar in this area.